Metode Dakwah Majelis Ta’lim Syababul Kheir di Kota Bogor - Hidayatulloh, Rahmawan (Tadbir: Jurnal Manajemen Dakwah, 2024)
Based on an exploration of the truth that is often found in the city of Bogor regarding the useless activities of teenagers. Grouping with children of the same age in several places until late at night. The presence of the Syababul Kheir Ta'lim Council has become one of the assemblies that has been quite active in preaching since 2010, many young people have joined and sat on the Syababul Kheir Ta'lim Council. Habib Mahdi Assegaf is the caretaker and leader of the Syababul Kheir Ta'lim Council. This article aims to determine the delivery of da'wah messages using several da'wah methods, including the bil verbal, hil hal, bil qolam and bil mau'idzoh hasanah methods. Apart from that, his preaching promotes the values of love of prayer. The research method used in this research is a descriptive qualitative approach. The data collection techniques used were interviews, observation, documentation. This article reveals that the preaching of the Syababul Kheir Ta'lim Council is a new breakthrough in constructing the way of thinking of the people from children to adults in reciting the Koran and praying to the Prophet Muhammad SAW.